Modification of Mesoporous Silica Surface by Immobilization of Functional Groups for Controlled Drug Release - Abdullah M. Alswieleh (Journal of Chemistry)
This paper introduces the synthesis of mesoporous silica nanoparticles (MSNs) with three different groups such as amine, thiol, and sulfonic acid, along the internal surface. Trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride was used to modify the external surface of the nanomaterials. Such materials allow control of the drug release from MSN pores. Multifunctional MSNs were loaded with doxycycline (Doxy) to study their capacities and uploading time. The loading profile indicates that sulfonic groups in the internal surface were the most efficient surfaces with a loading capacity of ca. 35% in 90 min in acidic media.